2017
DOI: 10.1680/jgele.17.00063
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of epoxy resin-grouted sand under monotonic or cyclic loading

Abstract: The main objective of this study is to investigate the use of an amino-based epoxy resin as a new chemical grout with different resin-to-water ratios on the static and cyclic behaviours of medium–fine sand. To evaluate the effect of grouting on the static behaviour of grouted sand, unconfined compression tests were performed on specimens at different curing ages. The cyclic behaviour of grouted sand was investigated in stress control mode at a frequency of 1 Hz with different load amplitudes. The laboratory te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The elastic modulus was determined using the values from the linear segment of the compressive stress-strain curve. Previous research (Anagnostopoulos et al, 2014;Anagnostopoulos and Sapidis, 2017) has shown that epoxy resin grouted sands gain most of their final strength after 90 days of curing, after which noticeable improvement is not observed. For this reason, the current experimental program has studied the strength development of grouted specimens at curing ages up to 90 days.…”
Section: Methodsmentioning
confidence: 94%
“…The elastic modulus was determined using the values from the linear segment of the compressive stress-strain curve. Previous research (Anagnostopoulos et al, 2014;Anagnostopoulos and Sapidis, 2017) has shown that epoxy resin grouted sands gain most of their final strength after 90 days of curing, after which noticeable improvement is not observed. For this reason, the current experimental program has studied the strength development of grouted specimens at curing ages up to 90 days.…”
Section: Methodsmentioning
confidence: 94%
“…The epoxy resin employed in this study is a two-component water soluble commercial product widely distributed in Greece. Bisphenol A (epichlorhydrin) is the epoxy resin (part A), with an average molecular weight of approximately 700, and aliphatic gly-cidylether (part B) is the reactant agent for the polymerisation of the resin [16,[18][19][20]23]. According to the manufacturer, the optimal mixture ratio (by weight) of the two parts is A:B = 3.…”
Section: Methodsmentioning
confidence: 99%
“…These tests showed a significantly higher compressive strength and elastic modulus of 10 MPa and 1,200 MPa, respectively. Anagnostopoulos et al [18,19] evaluated the mechanical properties of a medium siliceous sand prepared in two different relative densities D r of 50 and 90% and grouted with different ER compositions. They demonstrated that the improvement of strength parameters depends directly on D r and the epoxy resin to water (ER/W) ratio.…”
Section: Introductionmentioning
confidence: 99%
“…These specimens were employed in unconfined compressive strength tests after 3, 7, 30, 90 and 180 days of curing, in order to evaluate the increase of compressive strength and elastic modulus with time, as well as, unconfined creep strength tests after 180 days of curing. Although past research [14,16,19] reported that, for curing periods higher than 90 days, the polymerisation rate dramatically drops, resulting in marginal strength improvement, it was decided to investigate the mechanical properties of treated sands at curing ages of up to 180 days. This decision was made because the grouts utilised in this study had higher ER/W ratios than those of the grouts referred to in past studies, a fact that could influence the duration of the polymerisation reactions, resulting in the extension of the hardening process of polymer films beyond 90 days.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…More recently, some investigators have suggested two-component water soluble epoxy resin emulsions, which are among the most widely applied polymeric compounds in many construction and building restoration projects [8,9,10,11], as grouting agents that can significantly improve the properties of weak soils. According to the previous research activity 2 [12,13,14,15,16,17,18,19], these chemical substances enhance the mechanical properties (compressive strength, elastic modulus, shear strength, toughness, creep strength and liquefaction resistance) and reduce the permeability and compressibility of grouted soils. However, there is still a need for broadening the research, in order to highlight the effect of some key factors (mainly the mean grain size d50, the uniformity coefficient cu and the type of soil) on the properties of the grouted soil, as well as, the impact of moisture condition on the mechanical behaviour of grouted soils under static loading.…”
Section: Introductionmentioning
confidence: 99%